2020
DOI: 10.1002/advs.201902398
|View full text |Cite
|
Sign up to set email alerts
|

Human Platelet Lysates‐Based Hydrogels: A Novel Personalized 3D Platform for Spheroid Invasion Assessment

Abstract: Fundamental physiologic and pathologic phenomena such as wound healing and cancer metastasis are typically associated with the migration of cells through adjacent extracellular matrix. In recent years, advances in biomimetic materials have supported the progress in 3D cell culture and provided biomedical tools for the development of models to study spheroid invasiveness. Despite this, the exceptional biochemical and biomechanical properties of human‐derived materials are poorly explored. Human methacryloyl pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 87 publications
0
41
0
Order By: Relevance
“…PLMA hydrogels have been shown to adequately support human stem cell adhesion and proliferation [ 9 , 19 ]. Before studying the effect of the presence of MSNCaPDex on stem cells differentiation, we evaluated the viability and adhesion of hBM-MSCs in the new PLMA hydrogel nanocomposite.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…PLMA hydrogels have been shown to adequately support human stem cell adhesion and proliferation [ 9 , 19 ]. Before studying the effect of the presence of MSNCaPDex on stem cells differentiation, we evaluated the viability and adhesion of hBM-MSCs in the new PLMA hydrogel nanocomposite.…”
Section: Resultsmentioning
confidence: 99%
“…PLMA hydrogels have shown to support distinct human-derived cell cultures, namely human mesenchymal stem cells, osteoblasts, and different bone osteosarcoma cell lines. Remarkably, encapsulated cells could also perform important biological processes such as growth, sprouting, and migration [ 9 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…By measuring the area of the spheroid and the length of invasion, the ability of each cell type to invade different cells can be evaluated ( Figure 1 ). 12 By harboring different types of cells and intervening with them to simulate the microenvironment of specific diseases, these models are cheaper and more reproducible than animal models. Briefly, the 3D cellular constructs are generally fabricated in a facile way, in which the centrifuged cells are initially stored in conical tubes or multi-well plates in pellets by centrifugation, forming a spherical culture system.…”
Section: Construction Of 3d Articulation Modelsmentioning
confidence: 99%
“… 13 In another instance, the experimental results showed that the expressions of Sox9 and Col2a1, as well as aggrecan mRNA in cartilage culture, significantly improved the ability of sediment culture cells. 14 , 15 In addition to suspension drop culture of cell alone, some cellularized spheres embedded in agar and collagen have been fabricated, in which these 3D models further simulated the physiological interactions, metabolism, growth, and metastasis of cells, 16 for instance, breast carcinoma 12 and lung cancer. 17
Figure 1 Schematics of 3D spheroids encapsulation to study cell spheroid invasiveness.
…”
Section: Construction Of 3d Articulation Modelsmentioning
confidence: 99%
“…[ 83 ] In fact, hydrogels architecture/porosity, [ 84 ] shape, spatial distribution of cell adhesion motifs, [ 85 ] mechanical cues, [ 86,87 ] and chemical composition can all be controlled to generate appropriate microenvironments for cancer cells proliferation and 3D microtumors formation. [ 14,81,88–92 ] Moreover, the cellular arrangement inside hydrogel networks might influence drug response and cellular behavior. [ 93 ] Monteiro et al.…”
Section: Hydrogels and The Tumor Microenvironment Ecmmentioning
confidence: 99%